PREVALENCE AND RISK FACTORS OF HEMOPHILUS INFLUENZA TYPE B MENINGITIS: ROLE OF VACCINATION AND SOCIAL DEMOGRAPHY IN THE PATHOGENESIS - MUHAMMAD, S; IQBAL, J; SHAH, SH; KHAN, A; BASIT, A; SHAH, PA (Biological and Clinical Sciences Research Journal, 2023)
Bacterial meningitis is a condition caused by a bacterial infection in the meninges that results in inflammation. The causative agent varies according to age and other related factors. Hemophilus Influenza type B (Hib) is the most common cause of meningitis in children. This study aimed to determine the prevalence of H. influenza meningitis, the role of vaccination, and demographic factors in the etiology of Hib meningitis. Using a cross-sectional design, the study was conducted at the Pediatrics department of Ayub Teaching Hospital, Abbottabad, for six months, from 19-9-2023 to 19-3-2024. After obtaining ethical approval from the IRB of Ayub Teaching Hospital Abbottabad, a cross-sectional study was conducted, and 143 patients who met the inclusion criteria were included in the study. Hib vaccination status was confirmed by history and the presence of a vaccination card. Cerebrospinal fluid (CSF) was collected and sent for analysis, including microscopy and culture. The mean age of the patients was 44.92±51.48 months, with a male-to-female ratio of 1.38:1. Seventy (49.65%) patients were fully vaccinated against the Hib virus. The study results showed that H. influenza growth on CSF culture was noted in 14 (9.79%) patients. The Hib positive status of these cases was significantly associated with gender, residential area, and socioeconomic class of the patient at p values of 0.005, 0.047, and 0.041. In conclusion, despite the use of conjugate vaccine, Hib remains a cause of meningitis, and the pathogenesis of Hib meningitis is associated with gender, residential category, and socioeconomic class of the patient.